Analisis Technology Acceptance Model (TAM) terhadap Implementasi Google Classroom pada SD Islam Terpadu Al-Muthmainnah Jambi - Suroto (JOURNAL VISION TECHNOLOGY (V-TECH), 2021)
The online learning system as a form of utilizing information technology at SD Islam Terpadu Al Muthmainnah Jambi has been implemented since early 2020 as a response to the impact of the COVID-19 pandemic. This study aims to determine the level of acceptance in the implementation of Google Classroom as an online learning facility at SD Islam Terpadu Al Muthmainnah with the TAM method which is one of the most influential technology acceptance theories in the world of Information Technology.